Effect of Washing Process on the Magnetic Property of Sm2Fe17 Nanopowder Prepared by Modified Reduction-Diffusion Process - Choi, Joon Phil; Kim, Yongrae; Shin, Dongwoon; Jung, Min-Kyo; Lee, Pil-Ho; Lyu, Hyun-Gon; Yun, Joon-Chul (Archives of Metallurgy and Materials, 2026)
This study investigates the influence of an improved washing process on the magnetic properties of Sm2Fe17 nanopowders synthesized via modified reduction-diffusion (MRD) process. In particular, hydrazine (N2H4) was used to reduce dissolved oxygen in deionized (DI) water, aiming to minimize oxidation during the removal of byproduct CaO. Compared to conventional DI water washing, the N2H4-treated process significantly reduced the oxygen content in the nanopowder from 2.53 wt.% to 0.85 wt.%, while also lowering residual Ca from 0.56 wt.% to 0.32 wt.%. As a result, the saturation magnetization (Mₛ) increased significantly from 73.9 emu/g to 127 emu/g, and coercivity (Hc) remained stable around 1150 Oe. These results highlight the critical role of wash water chemistry in preserving the intrinsic magnetic performance of Sm2Fe17 nanopowders and optimizing their suitability for permanent magnet applications.